Exploration of Strategies to Enhance the Character Education of Students for the Development of High-Quality Indonesian Human Resources - Mila Bestari; Nurhayati (Enigma Institute, 2023)
An in-depth examination of character education approaches can enhance our comprehension of how to cultivate people with qualities such as integrity, ethics, empathy, and excellent social skills. By employing effective character education strategies, we can facilitate students' comprehension of the esteemed principles of our nation and steer them towards being proactive citizens who contribute to the construction of a more prosperous future for Indonesia. The literature search was conducted on multiple databases, including PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to explore ways for cultivating character education in pupils to develop exceptional human resources. The character education of students is a crucial element in shaping people who are accountable, moral, and make constructive contributions to society. Educators and other people have a crucial responsibility to exemplify exemplary conduct and foster positive moral qualities in children. It is imperative that they demonstrate unwavering consistency in displaying their moral principles. Utilizing narratives, parables, and ethical anecdotes aids students in comprehending character virtues in a captivating and emotionally stimulating manner. These narratives foster emotional connections and facilitate students' introspection about their individual experiences. Facilitating chances for dialogue on moral and character values, as well as encouraging students to contemplate their own personal experiences, proves to be a highly effective approach to fostering a profound comprehension of character values among students. This promotes profound comprehension and the cultivation of analytical reasoning abilities. By implementing a well-organized character program with a specialized curriculum, we can ensure that character education becomes a fundamental aspect of the student's educational journey. This encompasses various aspects such as academic disciplines, non-academic activities, professional development for educators, and engaging parents.